Decision Support System (DSS) dengan Berorientasi -Solver - Rezty Amalia Aras (Pusat Riset dan Inovasi Nasional, 2022)
A Decision Support System (DSS) or decision support system is part of a computer-based information system (including knowledge-based/knowledge management systems) that is used to support decision-making within an organization or company. can also be said as a computer system that processes data into information to make decisions on specific semi-structured problems. In this paper, we try to solve a simple DSS with Microsoft Excel by using Solver.